Competition Policy On Online Taxi In Indonesia - Silalahi, Udin (UI Scholars Hub, 2019)
The presence of application-based taxis such as Grabcar and Gocar is a challenge for conventional taxis. Its existence can be reduced to conventional taxi company turnover. On March 22, 2016 thousands of conventional taxi drivers held a demonstration against the existence of online taxis, because online taxis were declared in violation of the Traffic Law and consequently the streets in Jakarta were chaotic. The existence of online taxis cannot be avoided any more, due to technological developments. Online taxis provide benefits and convenience for passengers in ordering and the rates are cheaper than conventional taxi rates. Anyone who has a cellphone and downloads the application, can order the online taxi and pick him up at the place where the passenger booked it. Therefore, the Government through the Ministry of Transportation issued Ministerial Regulation No. 32/2016 which recognizes the existence of online taxis in Indonesia and this Ministerial Regulation is revised through Ministerial Regulation No. 26/2017 and revised again to become Ministerial Regulation No. 108/2017.